Molecular interactions between apigenin and starch with different amylose/amylopectin ratios revealed by X-ray diffraction, FT-IR and solid-state NMR. (15th June 2023) - Ma, Yunxiang; Chen, Zidi; Wang, Zhipeng; Chen, Ruixi; Zhang, Shenggui
Abstract: Starch can readily form complexes with polyphenols. However, its two components, namely amylose and amylopectin, differ significantly in their ability to complex with phenolic compounds. Given that the mechanism of their interaction is still poorly studied, this work investigated intermolecular interactions between apigenin and starch with different amylose/amylopectin ratios using 1 H NMR, FT-IR, XRD, DSC and solid-state NMR. Results showed that corn starch with high amylose/amylopectin ratios had a better complexing ability and higher complexing index with apigenin than amylopectin. Besides, solid-state NMR suggested that the molecular mechanism behind the strong intermolecular interactions between corn starch and apigenin involved hydrogen bonds. Furthermore, the detailed binding sites of hydrogen bonds, that linked by hydroxyl-starch and phenyl-apigenin were also confirmed by 1 H 13 C heteronuclear correlation (HETCOR) spectra. This study revealed the molecular mechanism on amylose/amylopectin complexing with apigenin and provides a theoretical basis for further developing polyphenols in starchy food. Graphical abstract: Unlabelled Image